Severe Pre-Eclampsia with Partial Hellp Syndrome in Multigravida Preterm Pregnancy - Ratu Nirmala Wahyunindita; Ratna Dewi Puspita Sari (Indonesian Journal of Global Health Research, 2022)
Preeclampsia is the second highest cause of maternal death in Indonesia. The incidence of preeclampsia in Indonesia is very high at 24%. West Java is a province in Indonesia with a high preeclampsia rate of 25%.Pre-eclampsia is a vascular endothelial dysfunction and vasospasm that occurs at gestational age above 20 months and is characterized by hypertension and proteinuria, with or without pathological edema. Severe preeclampsia (PEB) is characterized by a minimum of systolic blood pressure 160 mmHg or diastolic blood pressure 110, impaired liver function, progressive renal insufficiency, pulmonary edema, brain and visual disturbances, or thrombocytopenia. This research is descriptive observational with a case report approach. The aim of this research is to discuss updates on the occurrence, concept, pathophysiology, and management of preeclampsia. In the case reported, a female patient, aged 29 years G3P2A0, 36 weeks gestational age with severe pre-eclampsia, partial hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome in a multigravida preterm pregnancy with grade I obesity and a history of cesarean section 5 years ago. After evaluation, the patient complained of headache and heartburn. After confirmation, the fetus has IUGR, then active management with Transperitoneal Sectio Caesarea is chosen.